OS CONFLITOS, BARREIRAS E CONQUISTAS DAS RELAÇÕES DE GÊNERO NA EDUCAÇÃO INFANTIL - AS RELAÇÕES DOS EDUCADORES E EDUCADORAS DE UMA CRECHE - Lopes, Elsa Santana dos Santos (2010)
The present research is presented under a qualitative perspective, of an ethnographic character. It analyses the relations established among the educators which work with infantile education, under the scope of the genre relations. At first, it discusses the historical path of the infantile Education in the main Laws and Documents that guide the Brazilian Education under the gender scope. Next, in a reflexive course, the analysis is inspired into the studies of the gender category, and brings important reflections about its definition, as well as its historical, political and social context, according to the authors: Joan Scott, Guacira Lopes Louro, Fúlvia Rosemberg and Jane Soares de Almeida. The focus of the research is guided based on the relations which are established among the educators of the institutions of infantile education. And the repercussion of these relations in the infantile education. There are many conflicts and barriers in infantile education under the scope of genders. However throughout the years several goals were reached in the perspective of the relations of gender in this teaching approach. Analyzing the relations among educators of a day nursery, it was noticed that the relations established in the infantile education present themselves as one of the ways of introduction of boys and girls in a social life. And, to think about the interaction among peers, being them little or big, boys and girls and it is as giving an opportunity to the most diverse understandings about oneself, about the other and the reality.(AU)